SWIMMING EDUCATION IN SCHOOLS : A BIBLIOMETRIC ANALYSIS OF TRENDS AND DEVELOPMENTS - Soleh, Soleh; Fitri, Mustika; Paramitha, Sandey Tantra; Apriady, Hilmy (STKIP Singkawang, 2024)
This study investigates the trends and developments in swimming education in schools from 2010 to 2024 through a bibliometric analysis. Utilizing data from Scopus, this research analyzes publication trends, authorship contributions, and international collaborations in the field of school swimming education. The results reveal a significant increase in the number of publications, particularly over the last six years, indicating a growing awareness of swimming education's importance as an integral part of school curricula for safety, physical fitness, and character development. Key authors, including Kevin Moran and Amy E. Peden, were found to contribute substantially to the literature, particularly on water safety and swimming skills. The United States, Australia, and the United Kingdom emerged as leading contributors, with the U.S. positioned as a central node in international collaboration networks. Furthermore, keyword analysis highlighted themes such as “swimming education,” “water safety,” and “physical health,” underscoring the focus on skill development and student safety.Overall, this study highlights the critical role of swimming education in forming resilient, health-conscious young individuals and underscores the need for policies that support accessible swimming programs in schools globally. These findings provide a foundation for further research and policy-making aimed at enhancing the effectiveness and reach of swimming education in educational settings worldwide.